Effect of strength and stiffness distributions on the displacement demands of asymmetric reinforced concrete buildings / Suhailah Mohamed Noor - Mohamed Noor, Suhailah (Institute of Graduate Studies, UiTM, 2016)
Torsional response characteristics of forty building models of elastic and inelastic asymmetric reinforced concrete buildings were studied by analyzing the near-fault and far-fault ground motions recorded during seven-pairs of recent earthquakes. The strength and stiffness eccentricities are the main parameters used in the present study contributing to the strength and stiffness distributions of building models under five mainmodels and eight submodels, respectively. The displacement demands of all buildings under the stiff and flexible sides were obtained from the analysis due to different values of fundamental period of vibrations as well as behavior factors by using RUAUMOKO-3D program before raw data of lateral displacement at each node were extracted using FORTRAN program. All data were then summarized in accordance to the strength and stiffness distributions in order to determine the impact of either strength distribution or stiffness distribution to the torsional behavior of one-story asymmetric reinforced concrete buildings. The torsional behavior of all building models were presented in terms of the normalized displacements at the stiff and flexible sides by the ratio of the maximum lateral displacement at the stiff and flexible sides to the maximum lateral displacement at the center of the building models…